Cross-European initial survey on the use of mathematical models in food industry - Djekic, Ilija; Mujčinović, Alen; Nikolić, Aleksandra; Jambrak, Anet Režek; Papademas, Photis; Feyissa, Aberham Hailu; Kansou, Kamal; Thomopoulos, Rallou; Breisen, Heiko; Kavallieratos, Nickolas G.; Athanassiou, Christos G.; Silva, Cristina L.M.; et al. (My University, 2019)
Mathematical modelling plays an important role in food engineering having various mathematical models tailored for different food topics. However, mathematical models are followed by limited information on their application in food companies. This paper aims to discuss the extent and the conditions surrounding the usage of mathematical models in the context of European food and drinks industry. It investigates the knowledge, nature and current use of modelling approaches in relation to the industry main characteristics. A total of 203 food companies from 12 European countries were included in this research. Results reveal that the country where the company operates, and size of the company, are more important predictors on the usage of mathematical models followed by the type of food sector. The more developed countries are positioned at the higher level of knowledge and use of available models. Similar pattern was observed at the micro level showing that small or medium sized companies exhibit lack of knowledge, resources and limiting usage of models.
Keywords: Mathematical models; Food industry; Knowledge in modelling; Usage of models